Clinical, pathological and virological aspects of fatal West Nile virus infections in ten free‐ranging goshawks (Accipiter gentilis) in Germany. Issue 2 (13th August 2020) - Feyer, Sina; Bartenschlager, Florian; Bertram, Christof A.; Ziegler, Ute; Fast, Christine; Klopfleisch, Robert; Müller, Kerstin
Abstract: West Nile virus (WNV), a zoonotic arbovirus, is a new epizootic disease in Germany and caused increasing avian and equine mortality since its first detection in 2018. The northern goshawk ( Accipiter gentilis ) is highly susceptible to fatal WNV disease and thus is considered as an indicator species for WNV emergence in European countries. Therefore, information regarding clinical presentation and pathological findings is important for identifying suspect cases and initiating further virological diagnostics. Between July and September 2019, ten free‐ranging goshawks were admitted to the Small Animal Clinic of the Freie Universität Berlin with later confirmed WNV infection. Clinical, pathological and virological findings are summarized in this report. All birds were presented obtunded and in poor to cachectic body condition. Most of the birds were juveniles (8/10) and females (9/10). Neurologic abnormalities were observed in all birds and included stupor (3/10), seizures (3/10), head tremor (2/10), head tilt (2/10), ataxia (2/10) and monoplegia (2/10). Concurrent diseases like aerosacculitis/pneumonia (7/10), clinical infections with Eucoleus spp. and Trichomonas spp. (3/10), trauma‐related injuries (3/10) and myiasis (2/10) were found. Blood analysis results were unspecific considering concurrent diseases. Median time of survival was two days. The most common pathological findings were meningoencephalitis (9/10), myocarditis (8/10), iridocyclitis (8/8) and myositis (7/10). WNV infection was diagnosed by real‐time quantitative reverse transcription polymerase chain reaction and confirmed by serology and immunohistochemistry.